PERILAKU OPORTUNISTIK PEMERINTAH KOTA MANADO ATAS PERUBAHAN DANA ALOKASI UMUM: SUATU KAJIAN KUALITATIF - Wenas, Jacqualine G.; Karamoy, Herman; Morasa, Jenny (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2020)
The purpose of this research examine the opportunistic behavior of the Manado City Government over changes in the General Allocation Fund (DAU) developed by Maryono (2013) and to obtain empirical evidence regarding the development of changes in the DAU allocation received from the Central Government and the opportunistic behavior of the Manado City Government over changes in the DAU throughout the 2014- Fiscal Year 2018. The approach used is a Qualitative Approach. Determination of key informants using purposive sampling techniques. Data collection techniques carried out by: Unstructured Interviews, Passive Participation Observation, and Documentation. Data analysis is performed through Data Reduction, Data Presentation, and Conclusion / Verification Activity. The results showed that the opportunistic behavior of the Manado City Government in responding to changes in the DAU: (1) Budgeting regional expenditure exceeds PAD as a source of regional income. Very high dependency behavior on DAU around 70 percent compared to PAD; (2) Non-proactive behavior towards developing the potential of resources to generate greater PAD contribution that exceeds or is balanced with regional expenditure expenditure, even though PAD can only finance 30 percent and is not fixed in nature; (3) Lack of developing a realistic attitude in formulating savings criteria in regional budgeting, especially savings in operational expenditure budgets to prioritize the use of the budget for the provision of community services; (4) Government's customary attitude to accept the fact that Manado City can only rely on the Service Sector due to the lack of natural resource potentialKeywords: Opportunistic Behavior, Local Government, General Allocation Funds.